National Football League playmakers reader - Polzer, Tim. (New York : Scholastic, 2006)
A reader featuring short biographies of six of the NFL's most popular players.
Tiki Barber -- Matt Hasselbeck -- Ben Roethlisberger -- Steve Smith -- Brian Urlacher -- Roy Williams.
At head of title: NFL.
1240
Keywords: Football players -- United States -- Biography -- Juvenile literature; Football players